Plastic film mulching with ridge planting alters soil chemical and biological properties to increase potato yields in semiarid Northwest China - Mingfu Shi; Yichen Kang; Weina Zhang; Xinyu Yang; Yanling Fan; Huifang Yu; Ruyan Zhang; Aixia Guo; Shuhao Qin (Chemical and Biological Technologies in Agriculture, 2022)
Abstract Background The growth of potato (Solanum tuberosum L.) is severely affected by the complex and variable soil environment, and film mulching has been widely used for potato growth in semiarid areas of western China. However, there are few studies on the effects of film mulching on soil quality and tuber yield in potato fields. Methods The effects of four mulching patterns (flat plot without film mulching, FP; flat plot with film mulching, FPM; ridge planting with half mulch, RPHM; ridge planting with full mulch, RPFM) on soil chemical and biological properties and potato tuber yield were investigated during two growing seasons (2018 and 2019) in the field. Results The results showed that compared with FP, the mulching treatments significantly increased the tuber yield of potato, with an increase of 3.7–20.77% and 7.89–26.35% in 2018 and 2019, respectively, and the yield of RPFM was higher than that of other treatments. In both growing seasons, RPFM significantly increased the contents of alkali-hydrolyzed N and available P, and the activities of soil urease, catalase, alkaline phosphatase, and sucrase. Bacterial and actinomycete counts were significantly higher in RPFM than those in the other treatments. Furthermore, RPFM significantly increased large potatoes and decreased small potatoes. Pearson’s correlation analysis revealed that soil alkaline dissolved nitrogen and actinomycete populations were the main factors affecting potato yield formation. Conclusions These results indicate that RPFM can improve the soil environment and further increase potato tuber yield, which is a viable option for potato production in semiarid areas. Graphical Abstract